MODERN EDUCATION AND PRAGMATISM IN MALAYSIA - Sakinah Munarwarrah Hashim (Journal of Islamic, Social, Economics and Development, 2023)
Since independence, Malaysia education system has undergone numbers of changes and modifications. As known to many, the British colonial authority left behind the former educational system. However, in 1961, there was a gradual transition from the British (English School) education system to a Malaysian school system focusing on unique Malaysian-oriented curriculum. In 1979, Tun Dr. Mahathir Mohammed, a former prime minister of Malaysia, introduced curriculum changes for the country's education system. He placed an emphasis on all levels of schooling on a holistic approach which includes intellectual, spiritual, physical, and emotional development for humans across all cognitive, affective, and psychomotor domains. As discussed above, Malaysia has already had a sound and stable educational system. However, in light of the current state of globalisation and recent insightful findings in relation to the world of education, it is necessary to implement pragmatism in Malaysia's education system in order to give students the best possible preparation for their futures. In particular, this study focuses on Malaysia's education system in light of the current state of the modern world, which is constantly changing and challenging. It is intriguing to see how pragmatism is applied and how things are going in Malaysian education landscape. The purpose of the study is to analyse and assess how pragmatism is applied in Malaysia's education system, specifically for Muslims. The elements and significance of pragmatism on education are further examined, and will interview people who have background of Islamic and non-Islamic background. And then followed by insightful discussion on pragmatism and Islamic education for Muslims.